Morphometric analysis of nasopalatine foramen in Sri Lankan population using CBCT - R.M. Jayasinghe; P.V.K.S. Hettiarachchi; M.C.N. Fonseka; D. Nanayakkara; R.D. Jayasighe (Elsevier, 2020)
Nasopalatine canal (NPC) is an important anatomical structure present in the anterior mid maxilla. It has the synonyms of incisive canal or anterior palatine canal. The objective of this study was to identify the morphometric characteristics of the NPC in group of Sri Lankan people using Cone beam computer tomography (CBCT) and to determine normal morphological course and anatomical variations. Fifty Maxillary CBCT images of anterior maxilla, obtained from the archives of the University Dental Hospital, Peradeniya were retrospectively analyzed to determine the position of the NPC. Morphology, canal dimension of NPC and its relation to the maxilla. Majority had a single opening (48%) or 2 openings (46%). Average diameter of the canal was 3.692 mm with a range of 2-6 mm. Majority of the canals had funnel shape and were vertically curved. Average length of canal was 12.142 mm and angulations of the curvature was 115.6940. Average antero-posterior diameter at nasal fossa was 2.852 mm, at mid-palate 2.366 mm and at hard palate 3.034 mm. Our findings were different from the findings reported in the literature. This may be due to the differences in ethnicity or limited size of sample. Within the limits of this study, we conclude that the form of the NPC is variable; predominantly funnel shaped with a single or two openings and with an average diameter of 3.7 mm in Sri Lankan population. Identification of variations in the position and shape will help in clinical practice specially in introducing local anesthetic block injections during dental treatment.